Study of positive and negative plasma catalytic oxidation of ethylene. Issue 12 (18th June 2017) - Van Wesenbeeck, K.; Hauchecorne, B.; Lenaerts, S.
ABSTRACT: The effect of introducing a photocatalytically active coating inside a plasma unit is investigated. This technique combines the advantages of high product selectivity from catalysis and the fast start-up from plasma technology. In this study, a preselected TiO2 coating is applied on the collector electrode of a DC corona discharge unit as non-thermal plasma reactor, in order to study the oxidation of ethylene. For both positive and negative polarities an enhanced mineralization is observed while the formation of by-products drastically decreases. The plasma catalytic unit gave the best results when using negative polarity at a voltage of 15 kV. This shows the potential of plasma catalysis as indoor air purification technology. GRAPHICAL ABSTRACT: